Implementasi NodeMCU dan Blynk Dalam Sistem Pendeteksi Kebakaran Berbasis IoT - Asronika, Nurlaily; Akyun, Alifiyul; Lutfiyah Mahmudah, Nadhifah; Wahyuningtyas, Rofiqoh; Nugroho Pramudhita, Agung (Journal Software, Hardware and Information Technology, 2024)
Fires can cause material losses and human lives. Therefore, an effective fire early detection system is needed to prevent greater losses. In this research, ESP8266 is used as a microcontroller to connect fire detection sensors such as KY-026 Fire Sensor and MQ-2 Smoke Sensor. This early fire detection system is also equipped with a buzzer as an alarm and NodeMCU as a platform to connect the system to the Internet network and Blynk as a medium to provide real-time fire notifications to users. Tests were conducted by comparing the response time and accuracy of fire detection at different distances. The test results show that the fire early detection system built has an average response time of 2 seconds and a detection accuracy rate of 95%.